1974
DOI: 10.1111/j.1365-2672.1974.tb00413.x
|View full text |Cite
|
Sign up to set email alerts
|

The Recovery of Indicator Bacteria on Selective Media

Abstract: Summary. The recovery of Pseudomonas aeruginosa, Escherichia coli, and Streptococcus faecalis from aqueous suspending media has been studied with a rich plating medium (trypticase‐soy agar) and selective media. Tap water was highly toxic to all strains investigated. Recovery of Ps. aeruginosa was most successful when phosphate buffer was the diluent. Phosphate buffer did not improve the recovery of E. coli. Streptococcus faecalis remained viable when suspended in double distilled water, deionized distilled wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

1981
1981
2002
2002

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 38 publications
3
22
0
Order By: Relevance
“…This observation suggested that media and techniques to enumerate injured indicator bacteria could be improved. Highly variable coliform recovery efficiencies from natural samples have been observed for some time (Hoadley and Cheng, 1974;Dutka and Tobin, 1976;Bissonnette et al, 1977). This finding may be explained by the data in Figure 23.1, which show a progressive discrepancy in efficiencies of enumeration for a variety of media as bacteria were exposed in a stressful aquatic environment.…”
Section: Detection and Occurrence Of Injured Indicator Bacteria In Drmentioning
confidence: 93%
See 2 more Smart Citations
“…This observation suggested that media and techniques to enumerate injured indicator bacteria could be improved. Highly variable coliform recovery efficiencies from natural samples have been observed for some time (Hoadley and Cheng, 1974;Dutka and Tobin, 1976;Bissonnette et al, 1977). This finding may be explained by the data in Figure 23.1, which show a progressive discrepancy in efficiencies of enumeration for a variety of media as bacteria were exposed in a stressful aquatic environment.…”
Section: Detection and Occurrence Of Injured Indicator Bacteria In Drmentioning
confidence: 93%
“…As early as 1935, there was evidence that chlorine caused a reversible form of bacterial inactivation (Mudge and Smith, 1935). Schusner et al (1971) convincingly described the reversible inactivation of E. coli by chlorine in foods, followed a few years later by two reports of the same process associated with tap water and wastewater (Braswell and Hoadley, 1974;Hoadley and Cheng, 1974).…”
Section: Disinfectantsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, misidentification of typical colonies as fecal coliforms on VRBL seems to be a problem. These fecal coliforms, which are not characteristic colonies on either medium, might be injured or physiologically compromised organisms that probably could not have survived exposure to 44 Ϯ 1°C but were able to repair themselves and grow at 37 Ϯ 1°C, even though some of them produced insufficient acidity and gas to be detected by the lactose fermentation assay (24,36). The typical colonies on VRBL and FCA, which do not produce gas from lactose, could also be stressed or late lactose-fermenting bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Disinfectants and other biocides used to treat water probably represent the major cause of bacterial injury in aquatic systems (Hoadley and Cheng, 1974;Camper and McFeters, 1979;. While bacterial lethality is the intended consequence of water disinfection, the application of disinfectants in ways that lead to sub-optimal biocidal activity promotes injury.…”
Section: Disinfectantsmentioning
confidence: 99%